2016
DOI: 10.1007/s00214-016-1983-9
|View full text |Cite
|
Sign up to set email alerts
|

Competition for water between protein (from Haloferax mediterranei) and cations $$\hbox {Na}^+$$ Na + and $$\hbox {K}^+$$ K + : a quantum approach to problem

Abstract: The competition between Na + and K + with a protein for water was investigated by using Density Functional Theory (DFT) calculations. The optimized potential energy curves have been made in the DFT, together with balanced basis sets of split valence Def2-SV(P). Initially, calculations were performed in order to know the organization of the hydration shell of the sodium and potassium ions, when up to sixteen molecules of water are added. The results indicate the structure and stability of these cations with wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The differences in the distribution of water in the solvation shell of the sodium and potassium without the presence of a protein have been the subject of several studies [3,25]. Such differences can increase when a protein is present, as we described in the case of a halophilic protein [13]; this phenomenon is also observed in the interaction of cations with the potassium channel, being reflected in the variation of the interaction energy of the cation with the water as it enters the channel [14].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The differences in the distribution of water in the solvation shell of the sodium and potassium without the presence of a protein have been the subject of several studies [3,25]. Such differences can increase when a protein is present, as we described in the case of a halophilic protein [13]; this phenomenon is also observed in the interaction of cations with the potassium channel, being reflected in the variation of the interaction energy of the cation with the water as it enters the channel [14].…”
Section: Discussionmentioning
confidence: 83%
“…The protein used in this study, as indicated above, is the open-form of voltage-gated sodium from Magnetococcus marinus MC1 [13] (NavMm) (protein ID in the RSC Protein Data Bank: 5HVX) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…These solutes help to maintain turgor, pressure, cell volume, and electrolyte concentration. They can be released into the external environment either by other producing microorganisms following a drop in osmolarity or by decaying plant, animal, or bacterial cells [5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%